Academician Evgeniy Nikolaevich Meshalkin (1916–1997) (on the 105th anniversary of his birth) - A. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
The outstanding cardiologist and cardiac surgeon Evgeny Nikolaevich Meshalkin was born on February 25, 1916 in the city of Yekaterinoslav, now Dnepropetrovsk. In 1918, the Meshalkin family moved to Rostov-on-Don, and in 1928 to Moscow, where Evgeny graduated from school in 1930, and then studied at the factory school at the Sickle and Hammer factory. In 1941, Evgeny Nikolaevich graduated from the 2nd Moscow Medical Institute and from August 1941 to May 1945 was a participant of the Great Patriotic War permanently in the field army. After demobilization from the army, E. N. Meshalkin worked from 1946 to 1956 at the department and at the clinic of Faculty Surgery of the 2nd Moscow State Medical Institute, headed by Academician of the USSR Academy of Medical Sciences A. N. Bakulev. In 1950, he defended his PhD thesis «Intubation anesthesia», and in 1953, his first monograph «Intubation anesthesia Technique» was published. Evgeny Nikolaevich is rightfully considered one of the founders of the Russian anesthesiology. In 1953, E. N. Meshalkin defended his doctoral dissertation «Probing and contrast study of the heart and major vessels». In conditions of moderate nonperfusion hypothermia, Yevgeny Nikolaevich successfully operated on complex heart defects, performed the insertion of mechanical prostheses for mitral and aortic insufficiency. From January 1956 to 1960, he was the head of the Department of Thoracic Surgery and Anesthesiology of the Central Institute of Advanced Medical Training (now the Russian Medical Academy of Postgraduate Education). E.N.Meshalkin owns 47 copyright certificates and patents, which are implemented not only in the Research Institute of Circulatory Pathology, but also in other cardiac surgery centers in Russia. Honorary citizen of Novosibirsk Evgeny Nikolaevich Meshalkin passed away on March 8, 1997 and was buried in Novosibirsk at the Southern Cemetery. In memory of the outstanding scientist, the Novosibirsk Research Institute of Circulatory Pathology was named after Academician E. N. Meshalkin.